Exploring the antifungal, antibiofilm and antienzymatic potential of Rottlerin in an in vitro and in vivo approach - Silva, Nagela Bernadelli Sousa; Menezes, Ralciane Paula; Gonçalves, Daniela Silva; Santiago, Mariana Brentini; Conejo, Noemi Chagas; Souza, Sara Lemes; Santos, Anna Lívia Oliveira; da Silva, Robinson Sabino; Ramos, Salvador Boccaletti [UNESP]; Ferro, Eloisa Amália Vieira; Martins, Carlos Henrique Gomes (Springer Nature, 2024)
Candida species have been responsible for a high number of invasive infections worldwide. In this sense, Rottlerin has demonstrated a wide range of pharmacological activities. Therefore, this study aimed to evaluate the antifungal, antibiofilm and antivirulence activity of Rottlerin in vitro against Candida spp. and its toxicity and antifungal activity in vivo. Rottlerin showed antifungal activity against all yeasts evaluated, presenting Minimum Inhibitory and Fungicidal Concentration (MIC and MFC) values of 7.81 to > 1000 µg/mL. Futhermore, it was able to significantly inhibit biofilm production, presenting Biofilm Inhibitory Concentration (MICB50) values that ranged from 15.62 to 250 µg/mL and inhibition of the cell viability of the biofilm by 50% (IC50) from 2.24 to 12.76 µg/mL. There was a considerable reduction in all hydrolytic enzymes evaluated, with emphasis on hemolysin where Rottlerin showed a reduction of up to 20%. In the scanning electron microscopy (SEM) analysis, Rottlerin was able to completely inhibit filamentation by C. albicans. Regarding in vivo tests, Rottlerin did not demonstrate toxicity at the therapeutic concentrations demonstrated here and was able to increase the survival of C. elegans larvae infected. The results herein presented are innovative and pioneering in terms of Rottlerin’s multipotentiality against these fungal infections.
Keywords: Antibiofilm; Antifungal activity; Caenorhabditis elegans; Hydrolytic enzymes; Rottlerin